A Study on Cattle Insurance in Villages of Gandhinagar District. Issue 2 (January 2014) - Trivedi, Jigna; Kunal Soni, Bindiya
Livestock enterprises are flourishing business of rural India and are interwoven in socio-economic fabric of villages. 62% of rural India largely depends on dairy farming, which provides supplementary income to crop farmers. Crop farming and cattle rearing are strategic business units of rural enterprise, which provides part-time occupation to women and make them empowered. In the study a noteworthy point was found that women were engaged in cattle rearing from childhood. Cattle must be protected against the various types of risk such as death, disease, epidemic episode, burglary, fodder risk, dry-period risk, and permanent total or partial disability to provide milk etc. It was very rare to see that all the cattle were insured. Cattle insurance was availed due the motivation of Village Cooperative Society (VCS). Insurance was sold on partneragent model and that too from a single company with whom VCS had a close tie-up. Lower amount of cattle valuation proved to be fatal in the event of death of the cattle and its replacement with new cattle, due to escalating prices. Broadening the riders and introduction of novel annuity or medi-claim plans would open up scope for cattle insurance business and safeguard the recipients against major risk inherent in cattle rearing.